Successful treatment with fumagillin of the first pediatric case of digestive microsporidiosis in a liver‐kidney transplant. Issue 6 (23rd October 2013) - Desoubeaux, G.; Maakaroun‐Vermesse, Z.; Lier, C.; Bailly, É.; Morio, F.; Labarthe, F.; Bernard, L.; Chandenier, J.
Abstract We report the first successful use, to our knowledge, of fumagillin alone in a pediatric patient to cure intestinal microsporidiosis in a liver‐kidney transplanted child. Detection of Enterocytozoon bieneusi in stool became negative from the first post‐therapeutic control, while digestive symptoms disappeared in 4 days. During a 9‐month follow‐up, polymerase chain reaction and direct examinations remained negative for microsporidia in her feces. No major undesirable effects were noted during the anti‐microsporidial therapy.